Legal Protection for Victims of Human Trafficking: Indonesian Migrant Workers Abroad - Fitri Setyo Rini; Rina Arum Prastyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Trafficking is currently a serious and urgent global problem. Indonesia itself is also a barn of human trafficking victims, especially related to the labor migration of Indonesian Migrant Workers (PMI) sent abroad. Many migrant workers are victims of exploitation and human rights violations due to human trafficking. Therefore, it is important to strengthen the protection of PMI rights through national and international legal frameworks. This research aims to analyze the legal framework for the protection of migrant workers as victims of human trafficking abroad. The method used is normative legal research by examining relevant national and international laws and regulations. The results show that Indonesia has a strong commitment through the ratification of various international legal instruments to protect migrant workers. However, law enforcement still faces various obstacles and there is a need for stronger cross-border cooperation. Therefore, a more comprehensive policy is needed to improve the protection of migrant workers.